Surface Activation and Pretreatments for Biocompatible Metals and Alloys Used in Biomedical Applications - Vivian Huynh; Ngan K. Ngo; Teresa D. Golden (International Journal of Biomaterials)
To improve the biocompatibility of medical implants, a chemical composition of bone-like material (e.g., hydroxyapatite) can be deposited on the surface of various substrates. When hydroxyapatite is deposited on surfaces of orthopedic implants, several parameters must be addressed including the need of rapid bone ingrowth, high mechanical stability, corrosion resistance, biocompatibility, and osseointegration induction. However, the deposition process can fail due to poor adhesion of the hydroxyapatite coating to the metallic substrate. Increasing adhesion by enhancing chemical bonding and minimizing biocoating degradation can be achieved through surface activation and pretreatment techniques. Surface activation can increase the adhesion of the biocoating to implants, providing protection in the biological environment and restricting the leaching of metal ions in vivo. This review covers the main surface activation and pretreatment techniques for substrates such as titanium and its alloys, stainless steel, magnesium alloys, and CoCrMo alloys. Alkaline, acidic, and anodizing techniques and their effects on bioapatite deposition are discussed for each of the substrates. Other chemical treatment and combination techniques are covered when used for certain materials. For titanium, the surface pretreatments improve the thickness of the TiO2 passive layer, improving adhesion and bonding of the hydroxyapatite coating. To reduce corrosion and wear rates on the surface of stainless steel, different surface modifications enhance the bonding between the bioapatite coatings and the substrate. The use of surface modifications also improves the morphology of hydroxyapatite coatings on magnesium surfaces and limits the concentration of magnesium ions released into the body. Surface treatment of CoCrMo alloys also decreased the concentration of harmful ions released in vivo. The literature covered in this review is for pretreated surfaces which then undergo deposition of hydroxyapatite using electrodeposition or other wet deposition techniques and mainly limited to the years 2000-2019.